Public Universities Funding in Nigeria: Challenges and way Forward - S., Dr. Olowonefa. G.; J., Ogunode, N.; Ohiosumua, Ohibime Ernest (European Journal of Life Safety and Stability (2660-9630), 2022)
This paper discussed challenges facing the funding of public universities in Nigeria. Secondary data were used to provide empirical support for the points raised in the paper. The secondary data were sourced from print materials and online resources on funding of universities in Nigeria. The paper concludes that adequate funding is key to the development of university education in Nigeria. Poor budgetary allocation, poor internally generated revenue, corruption insecurity problems and fall short in national revenue were discovered as the factors responsible inadequate funds in the universities in Nigeria. Also, effects of underfunding public universities were identified to include; inadequate infrastructural facilities, strike actions, poor quality of university education, poor research, ineffective training programme and shortage of academic staff. Based on this, the paper hereby recommended that the government should increase the funding of the Public universities in Nigeria. The government should develop the political will to implement the UNESCO recommendation of 26% for the sustainable development in the system.